Economic Sector Contribution and Tax Revenue: Does Per Capita Income Have a Role? - Wijaya, Suparna; Subiyantoro, Heru; Sutrisno, Sutrisno (KnE Social Sciences, 2024)
Taxes are the main source of state income. The research aims to examine the influence of the contribution of the service and the industrial sector on tax revenues. The difference in research is that it uses per capita income as a moderating variable. This research uses data from countries, such as Denmark, Finland, Iceland, Norway, and Sweden, which have several similarities in terms of prosperity, education, and a strong and stable economy. The data used comes from the World Bank and spans 2002-2019. The research results show that the contribution of the service sector, industry, and per capita income positively influences tax revenues. Supported by high tax rates, increasing donations to the service, and industrial sectors means that tax revenues are growing. Interestingly, using per capita income as a moderating variable negatively affects the service and industrial sectors’ tax revenues. With the moderating influence of per capita income, tax avoidance can grow in the service and industrial sectors. One of the tax avoidance measures is using a transfer pricing scheme. This was triggered by high tax rates and the Human Development Index (HDI). The higher the tax rate, the more loopholes the taxpayer will look for to avoid taxes, to lower the tax burden. A high HDI will enable a high level of tax knowledge. Apart from increasing tax compliance, a high level of tax knowledge will also allow tax avoidance. Keywords: economic sector contribution, tax revenue, per capita income